Peningkatan pemahaman dalam mengembangkan pembelajaran berdiferensiasi melalui metode pelatihan dan pendampingan pada guru sekolah dasar - Rintayati, Peduk; Riyadi, Riyadi; Kurniawan, Sandra Bayu; Kamsiyati, Siti (Universitas Sebelas Maret, 2022)
Abstract. The purpose of this study was to determine the increase in the understanding of elementary school teachers in developing differentiated learning through training and mentoring methods. This research is a quantitative descriptive study with a one-group pretest-posttest research design. The sample in this study were teachers in Kendal District, Ngawi Regency, East Java Province. The data collection technique used is a test. Data were analyzed using N-Gain. The results showed an increase in teacher understanding in developing differentiation learning. The pre-test showed an average score of 62.07 while the post-test increased with an average score of 85. Thus, teachers can improve their pedagogical skills in developing differentiated learning.